Protein extracts and aggregates forming in minced cod (Gadus morhua) during frozen storage - Tejada Yábar, Margarita; Careche, Mercedes; Torrejón, Purificación; Mazo, M. Luisa del; Solas, M. Teresa; García, M. Luisa; Barba, Carlos (Journal of Agricultural and Food Chemistry, 1996)
Natural actomyosin was extracted from frozen minced cod muscle stored for up to 62 weeks at -20 °C with 0.6 M NaCl, and the insoluble aggregates, when formed, were solubilized successively with 2% sodium dodecyl sulfate (SDS) and 2% SDS + 5% β-mercaptoethanol (ME) solutions, giving extracted fractions S1 (NaCl), S2 (SDS), and S3 (ME + SDS), precipitates insoluble in 0.6 M NaCl (P1) and 2% SDS (P2), and a precipitate not soluble in any of the agents used (P3). SDS polyacrylamide gel electrophoresis (SDS-PAGE) of fraction S1 showed that the proportion of the major proteins changed during frozen storage. Size exclusion chromatography snowed a decrease in the peak containing myosin heavy chain (MHC) and actin (Ac). Transmission electron microscopy (TEM) of S1 showed at the outset a filamentous morphology associated with globules interconnected crosswise. As storage progressed, the number and size of aggregates increased. In fractions S2 and S3, the major proteins detected by SDS-PAGE were MHC and Ac. TEM showed a greater abundance of ring-shaped structures than in S1. TEM of the insoluble fractions showed a sarcomerelike structure, more pronounced the milder the solubilizing treatment and the longer the storage time. This work is part of a project financed by the EU (Project FAR-UP3 647),Spanish ALI 92-1354-CE and ALI 94-0954-CO2-01-02. Peer Reviewed